How much is that guinea pig in the window? - Rocklin, Joanne; Johnson, Meredith (New York : Scholastic, 1995)
Mr Day's fourth grade class has a contest, recycling bottles and cans so that they will have enough money to buy a guinea pig.
K-3.
Keywords: Contests -- Fiction; Reading training, English (Elementary).; Recycling -- Fiction; Schools -- Fiction